RANCANG BANGUN SISTEM INFORMASI MANAJEMEN KOPERASI MENGGUNAKAN METODE WEB ENGINEERING (Studi Kasus : Primkop Kartika Gatam) - Yuri Rahmanto (Jurnal Data Mining dan Sistem Informasi, 2021)
Koperasi Primkop Kartika Gatam is a state-owned cooperative agency that provides savings and loan services to members and has an address at Jl Teuku Umar, No 85, Penengah, Kedaton, Bandar Lampung and has a total of 300 cooperative members. Based on the results of interviews with the head of the cooperative, Mrs. Ollivia Febrojaya, S.H, there were problems in the management process of processing savings and loan data, which as a whole was carried out using manual or recording processes such as loan applications and member data recording, saving and loan data recording. As a result, the integration of data between divisions cannot be carried out easily and the process of reporting data on deposits and loans is carried out repeatedly resulting in frequent delays in submitting reports on deposits and loans to the leadership. The next problem is that the process of calculating savings data is still using a calculator so that the impact is an error in calculating total savings and loans. This of course requires innovation regarding information technology that can be operated via the internet network using a website.So that the researcher provides a proposal to develop a cooperative management system that has several features such as online loan applications and can view the history of savings and loans and provides convenience with the calculation of the total recap and the amount of savings and loans automatically based on the date and month of the printed report.